An environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal and its preparation method
By adopting a multi-layer core-shell structure, the inner layer of FeCo@SiO2 core-shell particles and the outer layer of Co-Ce-O/graphene active layer, the existing catalyst has been solved, and efficient clean combustion and environmental protection have been achieved.
Patent Information
- Application Number
- CN202510272585.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-10
AI Technical Summary
The existing catalysts have low combustion efficiency, high dissolution of heavy metals and high recycling costs during coal-fired power generation, resulting in excessive environmental pollution and economic costs.
An environmentally friendly catalyst with a multi-layer core-shell structure is used. The inner layer is FeCo@SiO2 core-shell particles and the outer layer is Co-Ce-O/graphene active layer. The combustion efficiency and environmental protection are improved through magnetic recovery and high temperature stability.
The combustion efficiency of coal powder has been significantly improved to more than 98%, the dissolution of heavy metals has been reduced, the circulation stability and recycling efficiency of the catalyst has been improved, and ultra-low emissions and economic feasibility has been achieved.
Smart Images

Figure CN119771430A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to an environmentally friendly catalyst for promoting efficient and clean combustion of coal powder and a preparation method thereof. Background Art
[0002] Coal-fired power generation is the core mode of energy supply in my country. Its combustion process is prone to produce unburned carbon (fly ash carbon content ≥5%) and pollutant emissions. Although traditional commercial catalysts (such as V2O5-WO3 / TiO2) can partially improve combustion efficiency, they still have the following significant defects: Low combustion efficiency: Existing catalysts are limited by uneven dispersion of active components and insufficient thermal stability. The coal powder combustion efficiency is generally less than 90%, resulting in a large amount of unburned carbon residue, which not only wastes resources but also aggravates PM2.5 and CO2 emissions.
[0003] High recycling costs: Commercial catalysts need to be recovered through a complex water washing and filtration process, which consumes a lot of water (10 to 15 tons of water per ton of catalyst). In addition, the washing wastewater contains high concentrations of heavy metal ions, and the treatment cost is as high as more than 5,000 yuan per ton, which seriously restricts its economic feasibility.
[0004] The environmental risks are prominent: the accumulation of unburned carbon will reduce the thermal efficiency of the boiler, and the dissolution of heavy metals (such as V2O5 catalyst dissolution > 10 mg / L) will cause persistent pollution to the soil and water.
[0005] In view of the above problems, it is urgent to develop an environmentally friendly catalyst with high catalytic activity. Summary of the invention
[0006] The present invention innovatively designs a multi-layer core-shell structure, uses the inner layer FeCo@SiO2 core-shell particles to provide magnetic protection, and the outer layer Co-Ce-O / graphene active layer to enhance the catalytic performance, successfully breaking through the bottleneck of traditional technology. Experiments show that the catalyst prepared by the present invention has reached the industry-leading level in key indicators such as combustion efficiency, heavy metal dissolution inhibition and cycle stability, and provides a practical solution for coal-fired power plants to achieve ultra-low emissions. Specifically, the purpose of the present invention can be achieved through the following technical solutions: An environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal, the catalyst being a multi-layer core-shell structure; the multi-layer core-shell structure comprising an inner layer and an outer layer; the inner layer being FeCo@SiO2 core-shell particles; and the outer layer being a Co-Ce-O / graphene active layer.
[0007] Furthermore, the FeCo@SiO2 core-shell particles are prepared by the following steps: S1: Dissolve FeCl3·6H2O and CoCl2·6H2O in ethylene glycol, add 0.1 mol / L NaBH4 solution, stir at 80-85°C for 2-4h, filter and obtain FeCo nanoparticles; S2: Disperse FeCo nanoparticles in 75% by mass ethanol solution, add ethyl orthosilicate and 25% by mass ammonia water, stir at 50-55°C for 5-6h, filter, and obtain FeCo@SiO2 core-shell particles.
[0008] Furthermore, the dosage ratio of FeCl3·6H2O, CoCl2·6H2O, ethylene glycol, and 0.1 mol / L NaBH4 solution in S1 is 54-55 g:42-45 g:500 mL:0.7-1.0 L.
[0009] Furthermore, the dosage ratio of the FeCo nanoparticles, the ethanol solution with a mass fraction of 75%, the tetraethyl orthosilicate, and the ammonia water with a mass fraction of 25% in S2 is 30g:200mL:8.4-8.5g:10-12mL.
[0010] Furthermore, the preparation method of the catalyst comprises the following steps: FeCo@SiO2 core-shell particles and graphene oxide are added to pure water and ultrasonically dispersed for 1 to 2 hours, and then cerium nitrate and urea are added thereto, and a hydrothermal reaction is carried out at 80 to 90° C. for 8 to 10 hours to obtain a mixture, and then the mixture is dried at 120 to 150° C., and then calcined at 740 to 750° C. in an argon atmosphere for 2 to 3 hours. After calcination, the mixture is cooled to room temperature to obtain the catalyst.
[0011] Furthermore, the specific surface area of the graphene oxide is 800 m 2 / g.
[0012] Furthermore, the frequency of the ultrasonic dispersion is 40kHz and the power is 500W.
[0013] Furthermore, the usage ratio of pure water, FeCo@SiO2 core-shell particles, graphene oxide, cerium nitrate and urea is 500mL:25g:20-25g:15.5-16.0g:21-22g.
[0014] Beneficial effects of the present invention: The present invention provides an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal and a preparation method thereof. The catalyst prepared by the present invention is a multi-layer core-shell structure, wherein the inner layer is a FeCo@SiO2 core-shell; the outer layer is a Co-Ce-O / graphene active layer. The catalyst prepared by the present invention has the following advantages: (1) High-efficiency catalytic combustion: The Co-Ce-O / graphene active layer significantly improves the coal powder combustion efficiency to ≥98%, far exceeding commercial catalysts (<90%).
[0015] (2) Environmental protection and safety: SiO2 shell converts Fe 2+ and Co 2+ The dissolution amount dropped to below 0.05 mg / L, which is much lower than the shell-free control (6.87 mg / L), effectively avoiding heavy metal pollution.
[0016] (3) Convenience of magnetic recovery: The FeCo nanoparticles in the inner FeCo@SiO2 core-shell are magnetic materials with a high Curie temperature (>900°C). In the circulating fluidized bed mode, the low-temperature combustion of coal powder (850-900°C) can be controlled by material circulation. On this basis, the FeCo nanocore of the catalyst prepared by the present invention can maintain effective magnetism. After promoting the combustion of coal powder, the catalyst can be recovered by magnetism, thereby improving the recovery efficiency of the catalyst.
[0017] (4) High temperature stability: The Co-Ce-O layer and the SiO2 shell layer work synergistically. The SiO2 shell layer improves the high temperature stability of the FeCo magnetism through the coating effect. The Co-Ce-O has excellent high temperature resistance. The Co-Ce-O layer is bonded to SiO2 through the Si-O-Co bond to avoid mutual shedding. As a result, after 10 magnetic separation-pickling cycles, the efficiency of the catalyst in catalyzing coal powder combustion is always ≥95% and the combustion efficiency decay rate is ≤2.5%.
[0018] (5) Industrialization potential: The preparation process of the present invention is simple, the raw material cost is low, and it is suitable for large-scale application in ultra-low emission transformation of coal-fired power plants. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention will be further described below in conjunction with the accompanying drawings.
[0020] Figure 1 This is a TEM electron microscope characterization image of the FeCo@SiO2 core-shell particles in Example 2 of the present invention; Figure 2 This is a TEM electron microscope characterization image of the environmentally friendly catalyst for promoting efficient and clean combustion of coal powder in Example 2 of the present invention. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0022] A method for preparing an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal comprises the following steps: S1: 54 g of ferric chloride (FeCl3·6H2O) and 42 g of cobalt chloride (CoCl2·6H2O) were dissolved in 500 mL of ethylene glycol, and 0.7 L of 0.1 mol / L NaBH4 solution was added thereto. The system was heated to 80°C, stirred at constant temperature for 2 h, and then filtered to obtain FeCo nanoparticles; S2: 30 g of the FeCo nanoparticles prepared in S1 above were dispersed in 200 mL of 75% ethanol solution, and then 8.4 g of tetraethyl orthosilicate and 10 mL of 25% ammonia water were added thereto. The system was heated to 50°C, stirred at constant temperature for 5 h, and then filtered to obtain FeCo@SiO2 core-shell particles. S3: Add 25 g of the FeCo@SiO2 core-shell particles prepared in S2 and 20 g of graphene oxide (specific surface area 800 m 2 / g) and ultrasonically dispersed (40kHz, 500W) for 1h, then 15.5g of cerium nitrate (Ce(NO3)3·6H2O) and 21g of urea (CO(NH2)2) were added thereto, the system was heated to 80°C, and then hydrothermally reacted at a constant temperature for 8h to form a Co-Ce-O / graphene active layer to obtain a mixture, and then the mixture was dried at 120°C, and then calcined at 740°C in an argon atmosphere for 2h. After the calcination, it was cooled to room temperature to obtain an environmentally friendly catalyst for promoting efficient and clean combustion of coal powder. Example 2
[0023] A method for preparing an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal comprises the following steps: S1: 54 g of ferric chloride (FeCl3·6H2O) and 42.6 g of cobalt chloride (CoCl2·6H2O) were dissolved in 500 mL of ethylene glycol, and 0.8 L of 0.1 mol / L NaBH4 solution was added thereto. The system was heated to 80°C, and then stirred at a constant temperature for 4 h, and then filtered to obtain FeCo nanoparticles; S2: 30 g of the FeCo nanoparticles prepared in S1 were dispersed in 200 mL of 75% ethanol solution, and then 8.5 g of tetraethyl orthosilicate and 12 mL of 25% ammonia water were added thereto. The system was heated to 50 °C and stirred at constant temperature for 6 h. The FeCo@SiO2 core-shell particles were obtained by filtration. The TEM electron microscope characterization of the FeCo@SiO2 core-shell particles is shown in the attached Figure 1 ; S3: Add 25 g of the FeCo@SiO2 core-shell particles prepared in S2 and 25 g of graphene oxide (specific surface area 800 m 2 / g) and ultrasonically dispersed (40kHz, 500W) for 2h, then 15.5g of cerium nitrate (Ce(NO3)3·6H2O) and 21.5g of urea (CO(NH2)2) were added thereto, the system was heated to 80°C, and then the system was hydrothermally reacted at constant temperature for 10h to form a Co-Ce-O / graphene active layer to obtain a mixture, and then the mixture was dried at 120°C, and then calcined at 750°C in an argon atmosphere for 3h. After the calcination was completed, it was cooled to room temperature to obtain an environmentally friendly catalyst for promoting efficient and clean combustion of coal powder. The TEM electron microscope characterization of the catalyst is shown in the attached Figure 2 . Example 3
[0024] A method for preparing an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal comprises the following steps: S1: 55 g of ferric chloride (FeCl3·6H2O) and 45 g of cobalt chloride (CoCl2·6H2O) were dissolved in 500 mL of ethylene glycol, and 1.0 L of 0.1 mol / L NaBH4 solution was added thereto. The system was heated to 85°C, and then stirred at constant temperature for 4 h, and then filtered to obtain FeCo nanoparticles; S2: 30 g of the FeCo nanoparticles prepared in S1 were dispersed in 200 mL of 75% ethanol solution, and then 8.5 g of tetraethyl orthosilicate and 12 mL of 25% ammonia water were added thereto. The system was heated to 55°C, stirred at constant temperature for 6 h, and filtered to obtain FeCo@SiO2 core-shell particles. S3: Add 25 g of the FeCo@SiO2 core-shell particles prepared in S2 and 25 g of graphene oxide (specific surface area 800 m 2 / g) and ultrasonically dispersed (40kHz, 500W) for 2h, then added with 16.0g of cerium nitrate (Ce(NO3)3·6H2O) and 22g of urea (CO(NH2)2), the system was heated to 90°C, and then hydrothermally reacted at a constant temperature for 10h to form a Co-Ce-O / graphene active layer to obtain a mixture, and then the mixture was dried at 150°C, and then calcined at 750°C in an argon atmosphere for 3h. After the calcination, it was cooled to room temperature to obtain an environmentally friendly catalyst for promoting efficient and clean combustion of coal powder.
[0025] Comparative Example 1 Comparative Example 1 is the control group of Example 2. There is no SiO2 shell layer in Comparative Example 1. The preparation process is as follows: A method for preparing an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal comprises the following steps: S1: 54 g of ferric chloride (FeCl3·6H2O) and 42.6 g of cobalt chloride (CoCl2·6H2O) were dissolved in 500 mL of ethylene glycol, and 0.8 L of 0.1 mol / L NaBH4 solution was added thereto. The system was heated to 80°C, and then stirred at a constant temperature for 4 h, and then filtered to obtain FeCo nanoparticles; S2: 25 g of the FeCo nanoparticles prepared in S1 and 25 g of graphene oxide (specific surface area 800 m 2 / g) were mixed and ultrasonically dispersed (40kHz, 500W) for 2h, and then 15.5g of cerium nitrate (Ce(NO3)3·6H2O) and 21.5g of urea (CO(NH2)2) were added thereto, the system was heated to 80°C, and then the system was hydrothermally reacted at a constant temperature for 10h to form a Co-Ce-O / graphene active layer to obtain a mixture, and then the mixture was dried at 120°C, and then calcined at 750°C in an argon atmosphere for 3h. After the calcination, it was cooled to room temperature to obtain an environmentally friendly catalyst for promoting efficient and clean combustion of coal powder.
[0026] Comparative Example 2 Comparative Example 2 is the control group of Example 2. There is no Co-Ce-O layer in Comparative Example 2. The preparation process is as follows: A method for preparing an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal comprises the following steps: S1: 54 g of ferric chloride (FeCl3·6H2O) and 42.6 g of cobalt chloride (CoCl2·6H2O) were dissolved in 500 mL of ethylene glycol, and 0.8 L of 0.1 mol / L NaBH4 solution was added thereto. The system was heated to 80°C, and then stirred at a constant temperature for 4 h, and then filtered to obtain FeCo nanoparticles; S2: 30 g of the FeCo nanoparticles prepared in S1 above were dispersed in 200 mL of 75% ethanol solution, and then 8.5 g of tetraethyl orthosilicate and 12 mL of 25% ammonia water were added thereto. The system was heated to 50°C, stirred at constant temperature for 6 h, and then filtered to obtain FeCo@SiO2 core-shell particles. S3: Add 25 g of the FeCo@SiO2 core-shell particles prepared in S2 and 25 g of graphene oxide (specific surface area 800 m 2 / g) and ultrasonically dispersed (40kHz, 500W) for 2h, the system was heated to 80°C and subjected to constant temperature hydrothermal reaction for 10h to obtain a mixture, the mixture was then dried at 120°C, and then calcined at 750°C in an argon atmosphere for 3h. After the calcination, it was cooled to room temperature to obtain an environmentally friendly catalyst for promoting efficient and clean combustion of coal powder.
[0027] Test Example 1 The catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to performance tests. The performance test process is as follows, and the test results are shown in Table 1: (1) Heavy metal dissolution test: The catalyst was immersed in a nitric acid solution with a pH of 3 for 24 h, and the concentration of dissolved ions was detected by ICP-MS.
[0028] (2) Combustion efficiency test: Coal powder (median particle size 75 μm) and catalyst were mixed in a mass ratio of 100:1, placed in a tube furnace, and air was introduced. The temperature was raised to 800°C at a rate of 10°C / min and then burned at a constant temperature for 30 min. After the air introduction and heating were stopped, the mixture was naturally cooled to room temperature, the mass of the combustion residue was weighed, and the combustion efficiency (η) was calculated according to the following formula: η=(1-residue mass / initial mass)×100%.
[0029] (3) High temperature resistance test: Use a vibrating sample magnetometer (VSM) to measure the initial saturation magnetization intensity (Ms) of the catalyst, and then conduct a combustion efficiency test. After weighing, measure Ms again and calculate the magnetic attenuation rate: ΔMs = [(Ms initial - Ms after treatment) / Ms initial] × 100%.
[0030] (4) Cyclic stability test: The catalyst was subjected to 10 cycles of “combustion efficiency test → magnetic separation recovery → acid washing (pH=3 hydrochloric acid solution, 30 min) → drying (60°C, 6 h)”, and the combustion efficiency of the pulverized coal after 10 cycles was calculated (the calculation method is the same as above), and the combustion efficiency decay rate was calculated: Δη=[(ηinitial-ηafter 10 cycles) / ηinitial]×100%.
[0031] Table 1 Test results
[0032] From the data in Table 1, we can get: (1) The role of SiO2 shell: a. Antioxidation and magnetic protection: Comparative Example 1 (without SiO2 shell) Fe 2+ and Co 2+The dissolution amounts were 6.87 mg / L and 8.51 mg / L, respectively, which were much higher than those in Example 2 (0.05 mg / L and 0.08 mg / L), indicating that the SiO2 shell effectively isolated the FeCo nanoparticles from the external environment and significantly inhibited metal oxidation and ion dissolution.
[0033] b. High temperature stability: The magnetic attenuation rate of comparative example 1 is as high as 21.7%, while that of example 2 is only 4.5%, indicating that the SiO2 shell stabilizes the magnetism of FeCo at high temperatures and avoids magnetic loss due to oxidation.
[0034] (2) The role of the Co-Ce-O layer: a. Improved catalytic activity: The combustion efficiency of Comparative Example 2 (without Co-Ce-O layer) is only 78.7%, while that of Example 2 is 99.5%, indicating that the Co-Ce-O layer is a key active component for catalyzing efficient combustion of pulverized coal.
[0035] b. Enhanced structural stability: The Co-Ce-O layer is bonded to the SiO2 shell layer through the Si-O-Co bond (Example 2), preventing the outer layer from falling off, so that the combustion efficiency remains at 97.4% (decay rate 2.1%) after 10 cycles. However, the catalytic activity of Comparative Example 2 is insufficient, and the combustion efficiency cannot be improved.
[0036] (3) Synergistic effect: a. Dual protection mechanism: SiO2 shell provides a physical barrier to prevent FeCo oxidation, and Co-Ce-O layer enhances the overall structural stability through chemical bonding, which together reduce metal dissolution (Fe in Example 2 2+ The dissolution amount was only 0.7% of that in Comparative Example 1).
[0037] b. Optimization of high-temperature performance: The Co-Ce-O layer has both catalytic activity and high-temperature resistance (magnetic attenuation <5% at 800°C), and together with the SiO2 shell layer ensures that the catalyst remains efficient and stable in a high-temperature combustion environment.
[0038] c. Recycling economy: The magnetic recovery of FeCo nanoparticles and the catalytic activity of the Co-Ce-O layer work synergistically, so that the catalyst still maintains a combustion efficiency of ≥95% after 10 cycles, and the recycling cost is significantly reduced.
[0039] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.
[0040] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the invention, and the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. An environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal, characterized in that: The catalyst is a multi-layer core-shell structure, and the multi-layer core-shell structure includes an inner layer and an outer layer; The inner layer is FeCo@SiO2 core-shell particles; The outer layer is a Co-Ce-O / graphene active layer.
2. The environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal according to claim 1, characterized in that: The FeCo@SiO2 core-shell particles are prepared by the following steps: S1: Dissolve FeCl3·6H2O and CoCl2·6H2O in ethylene glycol, add 0.1 mol / L NaBH4 solution, stir at 80-85°C for 2-4h, filter and obtain FeCo nanoparticles; S2: Disperse FeCo nanoparticles in 75% by mass ethanol solution, add ethyl orthosilicate and 25% by mass ammonia water, stir at 50-55°C for 5-6h, filter, and obtain FeCo@SiO2 core-shell particles.
3. The environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal according to claim 2, characterized in that: The dosage ratio of FeCl3·6H2O, CoCl2·6H2O, ethylene glycol, and 0.1 mol / L NaBH4 solution in S1 is 54-55 g:42-45 g:500 mL:0.7-1.0 L.
4. The environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal according to claim 2, characterized in that: The dosage ratio of the FeCo nanoparticles, the ethanol solution with a mass fraction of 75%, the ethyl orthosilicate, and the ammonia water with a mass fraction of 25% described in S2 is 30g:200mL:8.4-8.5g:10-12mL.
5. A method for preparing an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal according to any one of claims 1 to 4, characterized in that: The following steps are involved: FeCo@SiO2 core-shell particles and graphene oxide are added to pure water and ultrasonically dispersed for 1 to 2 hours, and then cerium nitrate and urea are added thereto, and a hydrothermal reaction is carried out at 80 to 90° C. for 8 to 10 hours to obtain a mixture, and then the mixture is dried at 120 to 150° C., and then calcined at 740 to 750° C. in an argon atmosphere for 2 to 3 hours. After calcination, the mixture is cooled to room temperature to obtain the catalyst.
6. The method for preparing an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal according to claim 5, characterized in that: The specific surface area of the graphene oxide is 800 m 2 / g.
7. The method for preparing an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal according to claim 5, characterized in that: The frequency of the ultrasonic dispersion is 40 kHz and the power is 500 W.
8. The method for preparing an environmentally friendly catalyst for promoting efficient and clean combustion of pulverized coal according to claim 5, characterized in that: The usage ratio of the pure water, the FeCo@SiO2 core-shell particles, the graphene oxide, the cerium nitrate and the urea is 500 mL: 25 g: 20-25 g: 15.5-16.0 g: 21-22 g.
Citation Information
Patent Citations
Iron-based oxygen carrier with interlayer shell structure and capable of catalyzing direct combustion of coal, and preparation method for iron-based oxygen carrier
CN102533390A
Preparation method and application of noble metal@graphite layer core-shell structured electro-catalyst
CN106654307A
Hydrated mesoporous silica coated nano iron-cobalt bimetallic composite material and application thereof
CN112473672A
Preparation of Pd-based catalyst with core-shell structure and application of Pd-based catalyst in catalytic combustion of low-concentration methane
CN118892829A
Use of maganese compounds to inhibit both low and high temp. corrosion in utility and industrial farnance system
CN1508235A